MENENTUKAN PEMILIHAN OBJEK WISATA DI MAJALENGKA DENGAN MENERAPKAN SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN ALGORITMA NAIVE BAYES - M Makmun Effendi1; Aida Ratnasari2 (Teknik Informatika, Universitas Pelita Bangsa, 2019)
This study aims to assist tourists in choosing tourist objects, one of the famous tourist objects in Indonesia is in Majalengka. There are 3 famous objects in Majalengka, namely Paragliding, Tirta Indah, and Muara Jaya Waterfall. To determine the right choice, three criteria are used, namely: distance from the city center, visitor rates, and visitor convenience facilities. To determine the right choice, the approach is to use a decision support system through the Naïve Bayes Algorithm method which is one of the applications of the Bayes theorem in classification, Naive Bayes is based on a simplifying assumption that attribute values ​​are conditional independent of each other if an output value is given. To make it easier for visitors to make the right choice, a simple application was made using the PHP and My SQL programming languages ​​from the results of data processing using the Naïve Bayes method. The results of the classification of distance, rates and visitor convenience, the underarm typed one of the tourist attractions in Majalengka, namely Tirta Indah tourism,